Changing public threats and police priorities: How police chiefs respond to emerging threats - Ibbetson, Paul A. (Kansas State University, 2011)
Kansas police chiefs are a unique group of individuals. Because are they located throughout the various sized communities within the state, they have the potential to affect the daily lives of more people on a day-today basis than any other branch of law enforcement. The purpose of this study was to analyze how police chiefs prioritize emerging threats. In this study, using a purposeful sample, 40 semi-structured interviews were conducted with Kansas police chiefs across the state. These police chiefs were asked about their views on the biggest emerging threats they have observed within the last 10 years. They were also asked why certain threats become priorities and why others do not. Police chiefs were split on their thoughts of whether or not they believed resources should be allocated in their communities to defend against terrorism in Kansas. What was discovered during the research process went beyond learning about the process of change for threat prioritization, or what specific threats Kansas police chiefs think their communities are facing today. What was discovered was a deeper understanding of how police chiefs think when it comes to the relationship between police departments, police personnel, and community. As police chiefs addressed the processes by which they go about prioritizing emerging threats, they illuminated a unique strategy hierarchy for success that is centered on maintaining positive departmental perception. To maintain this perception, police chiefs work both officially and covertly within governmental structures and the public sphere to control how people think about their personnel and department. A prominent difference was seen in the physical proximity and accessibility of police chiefs to the community between small, medium, and large towns. In effect, to come to an understanding of the process of prioritization for emerging threats for Kansas police chiefs, it was necessary to understand these police administrators’ unique thought processes that they bring to the table when addressing important issues.
Keywords: Police chiefs; Kansas police chiefs; Emerging threats; Prioritizing threats; Perception; Terrorism; Criminology (0627); Social Research (0344); Sociology (0626)